Siderophore production by Pseudomonas aeruginosa FP6, a biocontrol strain for Rhizoctonia solani and Colletotrichum gloeosporioides causing diseases in chilli - Sasirekha, Bakthavatchalu; Srividya, Shivakumar (Agriculture and Natural Resources, 2016)
Siderophores are compounds secreted under low iron stress, which act as specific ferric iron chelating agents. Owing to their potential in the biological control of fungal phytopathogens, they may be used as an alternative strategy to chemical control. Pseudomonas aeruginosa FP6, previously isolated from rhizospheric soil samples was screened for its siderophore production on a chrome-azurol S agar plate. Change in the colour of the chrome-azurol S agar from blue to orange red confirmed the siderophore producing ability of P. aeruginosa FP6. The effects of various physicochemical parameters on siderophore production were studied. The maximum siderophore production was obtained in succinate medium (125 mM) followed by King’s B medium (105 mM). The presence of sucrose and mannitol increased the siderophore production. Yeast extract proved to be the most suitable nitrogen source. Media supplemented with Pb2+, Mn2+ and Mg2+ showed appreciable siderophore production as well as growth of cultures. An increase in the iron concentration favoured growth but substantially reduced siderophore production. The strain when tested for its in-vitro antagonistic activity against Rhizoctonia solani and Colletotrichum gloeosporioides on King’s B media, with and without FeCl3, showed a significant reduction in R. solani growth with FeCl3 supplementation compared to the control (without FeCl3), suggesting the role of siderophore mediated antagonism of R. solani. Antifungal activity was not influenced by FeCl3 in the case of C. gloeosporioides, suggesting the presence of other antagonistic mechanisms.